Current Developments in Monetary and Financial Law, Vol. 5. (International Monetary Fund, 2008)
The main theme of Volume 5 in this series is law and financial stability. The chapters cover many topics that enhance the reader's understanding of financial stability, as well as the many instruments available to promote it. The contributors discuss and analyze a range of issues such as, competing responsibilities of central banks and the institutional responses to past episodes of instability; the reasons for and against regulating hedge funds and derivatives, and the methods available for doing so; and the contributions of deposit insurance schemes, payments systems and securities settlement systems towards achieving financial stability. The relationship between laws proscribing money laundering and the financing of terrorism and the goal of financial stability is also discussed. The chapters in this edited volume are based on presentations from the tenth biennial seminar for legal advisors of central banks and member countries organized by the Legal Department and Institute of the IMF. The chapter authors include scholars, lawyers, representatives from the private sector, as well as officials of the IMF, other international organizations, and central banks.